Kudzu (Pueraria lobata) vine isoflavones, at a dose lower than the recommended daily allowance in Japan, prevents bone loss in ovariectomized mic - Tanaka, Teruyoshi; Tang, Hanjun; Umehara, Kazuya; Moriyama, Tatsuya; Kawamura, Yukio (FOOD SCIENCE AND TECHNOLOGY RESEARCH, 2023)
As the average longevity of humans increases, the number of patients with osteoporosis has also increased. Chemoprevention for osteoporosis, especially through food intake, may extend the healthy life expectancy. We previously reported that kudzu (Pueraria lobata) vine ethanol extract (PVEE) in the diet (20 mg/kg body weight/d) suppresses bone resorption and prevents bone loss in ovariectomized mice. However, experiments with lower PVEE concentrations are necessary to determine whether PVEE is a suitable functional food resource to improve osteoporosis. This study thus examined the effects of PVEE intake (2 or 5 mg/kg body weight/day, approximately 0.07 or 0.17 mg PVEE isoflavone/d/mouse) for 6 months. The dose was calculated on the basis of the recommended daily isoflavone allowance in Japan. Both 2 and 5 mg PVEE successfully prevented ovariectomy-induced bone loss in mice. These results indicated that PVEE was effective at these doses. Thus, PVEE has the potential to be a promising resource for osteoporosis-preventing functional foods.